Comparison of expectations-performance of Malaysian frontliners and satisfaction level on government decisions during the early stage of the COVID-19 outbreak - Mohd Amin, Siti Hajjar; Abdullah, Aida; Mohamed Ali, Abdul Jalil; Mohd Shafie, Siti Aishah; Mohd Wahid, Siti Daleela (Faculty of Administrative Science and Policy Studies, 2023)
This study investigates the gap between expectation and perceived performance of Malaysian frontliner and examines the citizen's satisfaction level with the government decision-making during the first wave of the pandemic. A cross-sectional survey of 346 Malaysian citizens uses snowball sampling until it reaches the appropriate sample size. The analysis of this study used Statistical Package for Social Science (SPSS) software such as the Kolmogorov-Smirnov Test for Normality and Wilcoxon's Signed-rank Test for matched pairs of perceived performance and expectations of five frontliner services, namely healthcare, police, armed, immigration, and maritime. Finally, this study used descriptive analysis to examine whether a disconfirmation met, exceeded, or below citizen expectations and satisfaction levels upon government decisions implementing several measures to curb the virus spread. The finding revealed that the perceived performance of all the frontliner services during the pandemic met and exceeded the respondents' expectations, and they were satisfied with the government's decisions. Based on the findings, future studies might consider using probability sampling and thus be able to conduct parametric analysis.